2013
DOI: 10.1371/journal.pgen.1003271
|View full text |Cite
|
Sign up to set email alerts
|

A Heterogeneous Mixture of F-Series Prostaglandins Promotes Sperm Guidance in the Caenorhabditis elegans Reproductive Tract

Abstract: The mechanisms that guide motile sperm through the female reproductive tract to oocytes are not well understood. We have shown that Caenorhabditis elegans oocytes synthesize sperm guiding F-series prostaglandins from polyunsaturated fatty acid (PUFA) precursors provided in yolk lipoprotein complexes. Here we use genetics and electrospray ionization tandem mass spectrometry to partially delineate F-series prostaglandin metabolism pathways. We show that omega-6 and omega-3 PUFAs, including arachidonic and eicosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
107
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(117 citation statements)
references
References 60 publications
(131 reference statements)
5
107
0
Order By: Relevance
“…Therefore, when genes involved in the synthesis are mutated, spermatozoa become partly defective in their relocation from the uterus into the spermatheca. [18][19][20] These phenotypes seem similar to those of spe-9 and spe-45 mutants, resulting in the incomplete sperm recruitment into the spermatheca. Currently the sperm prostaglandin-receptor(s) is not known, but SPE-9 and/or SPE-45 could function in the prostaglandin binding to spermatozoa and/or subsequent sperm reaction(s).…”
Section: Introductionmentioning
confidence: 59%
“…Therefore, when genes involved in the synthesis are mutated, spermatozoa become partly defective in their relocation from the uterus into the spermatheca. [18][19][20] These phenotypes seem similar to those of spe-9 and spe-45 mutants, resulting in the incomplete sperm recruitment into the spermatheca. Currently the sperm prostaglandin-receptor(s) is not known, but SPE-9 and/or SPE-45 could function in the prostaglandin binding to spermatozoa and/or subsequent sperm reaction(s).…”
Section: Introductionmentioning
confidence: 59%
“…PGs is available in Figure 4 and Table 2 3,16 . MS/MS data for mammalian eicosanoids is available at www.lipidmaps.org.…”
Section: Elegans Ms/ms Data For F-seriesmentioning
confidence: 99%
“…We have demonstrated that C. elegans synthesizes F-series PGs that guide motile sperm to oocytes 3,6,16 . F-series PGs derived from 20-carbon PUFAs with three, four, and five double bonds, comprising the F1, F2, and F3 classes, respectively have been identified 3,16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations